Fundamentals in Air Pollution From Processes to Modelling - Sportisse, Bruno; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This text is intended to be used in a lecture course for college students in air quality, with a focus on modelling challenges. The key current issues are discussed within six chapters: basic principles and classification of air pollution, radiative transfer, atmospheric boundary layer, gas-phase chemistry, aerosols and multiphase processes, and chemistry transport models and numerical simulation, respectively. The book starts with the basic principles of physics, chemistry and fluid mechanics, and is written in an understandable way for students. Through simple exercises and realistic problems (the answers are included) the state-of-the-science prevailing issues is investigated. Audience This book is intended for students in environmental science, meteorology, in the fields of climatic change and air pollution, geophysics and engineering. It may also be a good survey book for researchers active in the field. - Concise and comprehensive overview of air quality - Includes exercises and problem sets with detailed solutions
Primer for the Atmospheric Composition -- Atmospheric Radiative Transfer -- Atmospheric Boundary Layer -- Gas-Phase Atmospheric Chemistry -- Aerosols, Clouds and Rains -- Toward Numerical Simulation.
Keywords: Environmental sciences; Physical geography; Hydraulic engineering; Environmental protection; Environment; Atmospheric Protection/Air Quality Control/Air Pollution; Engineering Fluid Dynamics; Geophysics/Geodesy.